Drug Import Replacement Is a Perspective Direction of the Development of Russian Economy - K. D. Grigorieva (Управленческое консультирование)
The development of the domestic pharmaceutical industry as a science-intensive and hightech sector of the country’s economy is, among other things, a pledge of the drug safety of the state, especially in the conditions of a modern complex political situation and the sanctions regime. Solving related issues requires an integrated approach, active interaction of the state and participants in the pharmaceutical production and marketing market, a systemic approach and coordination of efforts to implement drug import substitution in the country, creating conditions for increasing the innovative activity of pharmaceutical companies. The main tendencies and directions of the industry development are considered in the article, the data on the course of drug import substitution in Russia are given.